The link between attitudes towards money and saving habits. Case study of housewives in kupang city - Maria, Maria; Lao, Hans A. (Jurnal Ekonomi, 2024)
This study aims to investigate the relationship between attitudes towards money and savings behavior among household financial managers in Kupang City. Attitudes towards money are defined through the dimensions of power-prestige, time retention, distrust, and anxiety. Referring to the fields of financial management and psychology, this research forms relevant hypotheses. Data were analyzed using multiple regression analysis with the assistance of SPSS 26 software. The results of the study indicate that savings behavior is significantly influenced by attitude factors towards money, including power-prestige, time retention, distrust, and anxiety. These findings provide deeper insights into how psychological factors can affect savings behavior within the context of household financial management. This study contributes to a more comprehensive understanding of the factors influencing savings behavior and their implications for household financial management.